Strategy of Excellent Madrasas in Improving School Quality: A Study at Madrasah Insan Cendekia Serpong, Banten - Mufasirul Alam; Sholichah, Aas Siti; Desy Ayu Ningrum; Fauziah, Erna; Samiudin, Lalu Muhammad (Scidac Plus, 2026)
This research aims to determine the strategies of superior madrasas in improving quality management. The research method uses qualitative methods with a field study approach. The research techniques use observation, interviews, and documentation. Madrasas are formal institutions that provide education at elementary, middle, and high school levels. One of the determinants of madrasah quality is quality management. Quality management is a systematic process used by organizations to ensure that products or services meet customer expectations and set quality standards. The quality management strategy used to improve the quality of madrasas is to strengthen the vision of madrasas to become strong and superior institutions. Apart from that, the curriculum is innovative and relevant which is strengthened by the support of both internal and external stakeholders. Apart from that, the quality and competence of teachers through training, workshops and training on teaching and teacher enrichment becomes a benchmark for the success of management, by strengthening students' abilities in the cognitive, affective, and psychomotor domains by strengthening various achievements in various fields of science and extracurricular activities. Teacher competence is also supported. digital literacy skills to adapt to today's digital world. Evaluation and monitoring are an inseparable part that can be carried out to assess the ability and involvement of school principals, teachers and students and administrative staff so that they can carry out quality management according to madrasah procedures.